Measurement and Thermodynamic Modeling for CO2 Solubility in the N-(2-Hydroxyethyl) Piperazine + Water System - Li, Simeng; Kang, Gern Woo; Chen, Jian (Frontiers in Energy Research, 2021)
Amine scrubbing is the most important technique for capturing CO2. The cyclic diamine N-(2-Hydroxyethyl) piperazine (HEPZ), a derivative of piperazine, with good mutual solubility in aqueous solution, low melting point and high boiling point, has the potential to replace PZ as an activator added in the mixed amine system to capture CO2. In this work, the solubility of CO2 in aqueous HEPZ solutions was determined for three HEPZ concentrations and four temperatures. The VLE data for HEPZ-H2O was obtained by gas-liquid double circulation kettle at pressure 30-100kPa. And the thermodynamic model for HEPZ-H2O-CO2 system was built in Aspen Plus, based on the electrolytic non-random two-liquid (ENRTL) activity model. The physical parameters for HEPZ, the interaction parameters for ENRTL, along with reaction constants of carbamate reactions, were regressed. Using thermodynamic model, the CO2 cyclic capacity, speciation with loading and heat of reaction for the CO2 capture system by the aqueous HEPZ solution are predicted and analyzed.